PERANAN DESA ADAT DALAM PENERTIBAN WARGA PENDATANG YANG MASUK DAN TINGGAL DI DESA ADAT PENGOSEKAN, KECAMATAN UBUD, KABUPATEN GIANYAR - I Nyoman Budi Palguna; I Wayan Eka Arta Jaya (Jurnal Hukum Mahasiswa, 2023)
The role of the Pengosekan Traditional Village in controlling the immigrant population cannot be separated from the pararem/awig-awig which regulates the control of the migrant population, but the role of the Pengosekan Traditional Village is declared ineffective because the officers in charge of controlling the immigrants in the Pengosekan Traditional Village have not implemented it properly. maximally, the apparatus referred to in enforcing the law enforcement of the immigrant population is pecalang. Based on the results of the analysis and conclusions in the discussion chapter, the authors propose the following suggestions: The Pengosekan Pecalang Traditional Village Prajuru must be more assertive in controlling the immigrant population. For village manners and krama tamiu who live in the Pengosekan Traditional Village to comply with the existing rules in the Pengosekan Traditional Village, help preserve the environment of the Pengosekan Traditional Villageand maintain the customs that have long developed in the Pengosekan Traditional Village. The importance of the rights and obligations of the Krama tamiu can maintain a balance between nature and the environment.